The Concept of The Senses According to Ibn Sina (Study on the Improvement of Faith) - Arraisi, Jarman; Rukmana, Fikri Hidayatul (Jurnal Diskursus Islam, 2023)
Among the factors that can improve the quality of one's faith is the knowledge that based on the correct epistemology. In this case, the information received by the mind is inseparable from the performance of the senses as the first perceiver capable of receiving sensations from sensory objects. By using the comparative descriptive analysis method, this paper aims to determine the concept of senses according to Ibn Sina in processing knowledge and its influence on faith. The discovery in this paper is that the concept of the senses is described by Ibn Sina as perfecting the function of reason in achieving knowledge with its performance in the form of a process of receiving sensory perceptions by external senses which are channeled to the internal senses so that humans can witness and contemplate the existence of God in achieving the truth that affects the quality of faith. In this case, it can be seen that Ibn Sina's concept of senses is different from the West which makes the senses the main source of knowledge without involving revelation.